Beyond document : essays on nonfiction film - Warren, Charles (University Press of New England, 1996)
In essays by eleven of America’s foremost writers, critics, and filmmakers, Beyond Document explores the full spectrum of nonfiction film and its creative possibilities. In addition to Charles Warren’s broad introductory history of the genre, the book takes a close look at ethnographic films, cinema-verité, memoir and autobiography, docudramas, essay films, and newsreels, from classics like Night and Fog and Nanook of the North to more recent important work like Film about a Woman Who. . ., Harlan County, U.S.A., Sans Soleil, and Forest of Bliss.